Lean manufacture na indústria automobilística - Shigio, Maurileno Marcos (2015)
Technology, Innovation, Sustainability, Cost Reduction, Quality, Continuous Improvement are words that today we hear everywhere; News, Schools, Shops, Industries. But what they have in common? What do they represent? This study aims to investigate the essence of Lean philosophy, its appearance, its his tory over the decades and their main tools. Which now become essential these days in any segment, especially when it comes to lean production. Within the large car companies they begin to be used from structuring phase. It is believed that its application should already be essential in the management of operational processes, and should be developed even if the company is still in the development process. In the case of Lean Production is understood that all management should be focused on small details, where when there is no daily monitoring in order to develop the culture no waste, the company will soon have a serious quality problem. And to avoid this the Lean philosophy follows strictly the types of waste that are: overproduction, waiting time, transportation, over-processing, inventory, motion and defects. Therefore, the aim is to research and describe a little about their history, which emerged, who began to use it and about every tool that is part of this philosophy. A brief bibliographic approach in the literature accompanying its evolution.